Developing an innovative pediatric integrated mental health care program: interdisciplinary team successes and challenges - Schweitzer, Jason; Bird, Anne; Bowers, Hilary; Carr-Lee, Nicole; Gibney, Josh; Schellinger, Kriston; Holt, Jasmine R.; Adams, Devin P.; Hensler, Domonique J.; Hollenbach, Kathryn (Frontiers in Psychiatry, 2023)
1.1 Introduction Children and adolescents often do not receive mental healthcare they need. By 2021, the complex impact of the COVID-19 pandemic, structural racism, inequality in access to healthcare, and a shortage of mental health providers led to an emergency in child and adolescent mental health in the United States. The need for effective, accessible treatment is more pressing than ever. Interdisciplinary, team-based pediatric integrated mental healthcare has been shown to be efficacious, accessible, and cost-effective. 1.2 Methods In response to youth mental health crisis, Rady Children’s Hospital-San Diego’s Transforming Mental Health Initiative aimed to increase early identification of mental illness and improve access to effective treatment for children and adolescents. A stakeholder engagement process was established with affiliated pediatric clinics, community mental health organizations, and existing pediatric integrated care programs, leading to the development of the Primary Care Mental Health Integration program and drawing from established models of integrated care: Primary Care Behavioral Health and Collaborative Care. 1.3 Results As of 2023, the Primary Care Mental Health Integration program established integrated care teams in 10 primary care clinics across San Diego and Riverside counties in California. Measurement-based care has been implemented and preliminary results indicate that patient response to therapy has resulted in a 44% reduction in anxiety symptoms and a 62% decrease in depression symptoms. The program works towards fiscal sustainability via fee-for-service reimbursement and more comprehensive payor contracts. The impact on patients, primary care provider satisfaction, measurement-based care, funding strategies, as well as challenges faced and changes made will be discussed using the lens of the Reach, Effectiveness, Adoption, Implementation and Maintenance framework. 1.4 Discussion Preliminary results suggest that the Primary Care Mental Health Initiative is a highly collaborative integrated care model that identifies the needs of children and adolescents and delivers brief, evidence informed treatment. The successful integration of this model into 10 primary care clinics over three years has laid the groundwork for future program expansion. This model of care can play a role addressing youth mental health and increasing access to care. Challenges, successes, and lessons learned will be reviewed.